Fire Retardancy Behavior of Polymer/Clay Nanocomposites - Zope, Indraneel Suhas (Springer Theses, Recognizing Outstanding Ph.D. Research, 2018)
This thesis investigates the early ignition behavior of polymer/clay nanocomposites, which are perceived as potential eco-friendly flame retardant systems. It examines the correlation between clay structural chemistry and high-temperature transformations with clay-assisted decomposition of organic macromolecules. In particular, it investigates the unique effects of metal ions like Mg2+, Al3+ and Fe3+ that are inherent in clays (smectite) on the combustion and thermo-oxidative decomposition of polyamide 6. The results indicate that metal ions present on/in montmorillonite platelets have preferential reactivity towards peroxy/alkoxy groups during polyamide 6 thermal decomposition. Lastly, a simple solution in the form of a physical coating on clay surface is proposed, based on the role of polymer-clay interfacial interaction.